Pichia kudriavzevii and Saccharomyces cerevisiae Inoculation Strategies for Cider Elaboration from Acidic Apples - Mazzucco, María Belén (2025)
Background: The cider industry is becoming an increasingly important segment of the apple fruit sector in Argentina. This study evaluated different inoculation strategies using two Patagonian strains to produce ciders with reduced malic acid and enhanced quality from acidic apple musts. Methods: Fermentations were performed using Pichia kudriavzevii NPCC1651 (isolated from cider) and Saccharomyces cerevisiae ÑIF8 (isolated from wine) in pure, simultaneous, and sequential inoculations. Viable cell counts, glucose and fructose consumption kinetics, and malic acid depletion were measured during fermentation, while physicochemical and aromatic profiles of the ciders were also analyzed in the final products. Results: P. kudriavzevii was capable of coexisting with S. cerevisiae until the final stages of fermentation, independently from the inoculation strategy employed. The simultaneous inoculation at a 1:1 ratio and the sequential inoculation initiated with S. cerevisiae showed the best performance. Both strategies produced ciders with high fermentative efficiency and elevated levels of lactic and succinic acids, isoamyl alcohol, 2-phenylethanol, isoamyl acetate, and 2-phenylethyl acetate while reducing acetic acid and ethyl acetate levels. These fermentations also achieved higher malic acid consumption compared to pure cultures. Conclusions: The simultaneous inoculation at a 1:1 ratio is proposed for further pilot-scale testing in natural acidic musts due to its operational practicality and its potential to produce ciders with reduced malic acid and improved sensory quality.